Complex endodontic and conservative treatment of a traumatized central incisor - Nicola Scotti; Damiano Pasqualini; Elio Berutti (Ariesdue, 2014)
Objectives: The functional recovery of a tooth with open-apex already endodontically treated is possible thanks to the materials, such as the MTA, able to produce an effective seal of the apex which can induce a restitutio-ad-integrum. A direct composite resin restoration may then provide a coronal seal immediate and effective in time, able to ensure a complete healing of the endodontic pathology. Materials and methods: The hereby-clinical case describes a combined approach (endodontic and conservative) for the aesthetic-functional recovery of a severely fractured upper incisor of a child of 11 years. Results and conclusions: At the control visit, after 12 months from the completion of the coronal restoration, a complete healing of periradicular bone tissue is observed through Rx. Clinical examination showed gingival tissue without inflammation and the probing depth is not increased, despite the presence of a cavity margin placed below the gingival margin.